THE INFLUENCE OF USING COMMUNITY LANGUAGE LEARNING (CLL) METHOD TOWARD STUDENTS’ SPEAKING ABILITY AT EIGHT GRADE OF SMP N 1 BATANGHARI - Fentari, Retno (Jurnal Review Pendidikan dan Pengajaran, 2025)
The objectives of this research is To find out whether the result student’s score by using CLL method maximal and to find out how far the result of influence using CLL method. The subject this research is the eight grade of SMP N 1 Batanghari.This research is to know influence of using CLL Method toward students’ speaking ability. the result shows that tCount = 2,8403; moreover the researcher looked at ttable for α = 1% shows ttble = 2.70 and for α = 5% shows ttable = 2.02  or it means tcount > ttable. It is obtained that Ha is accepted while Ho is rejected. It means that there is the influence of CLL Method toward students’ speaking ability. CLL Method is more effective, because by using CLL Method the mobilization of interaction of students is higher than by using Roleplay Method. So as the conclusion both of these Method are effective to be applied in teaching speaking for the eight grade of SMP N 1 Batanghari.